A study of laws and regulations to improve the reality of historical monuments and buildings with the surrounding urban landscape: Case Study: Al Shuwaiheen area in Sharjah City - Al-Maazmi, Khuloud; Jamhawi, Monther; Hussien, Aseel (Al-Adab Journal, 2025)
The development of the historic area has led to great concern for all those interested in preserving heritage and urban identity, as the heritage area is being expanded by creating and building modern projects and buildings next to it without resorting to detailed and unified laws or legislation that are clear to all concerned stakeholders. This study addressed the problem of “there are no detailed laws or rules specifying the building system for modern buildings adjacent to old buildings (historic areas) and there are no adequate regulations or studies that limit the rapid development in the archaeological area. Consequently, this resulted in a lack of harmony between the planning of Sharjah city. And there is no sufficient harmony in high level in the historical urban landscape of Al Shuwaiheen.”This study thesis addressed the development of detailed guidelines by the scientific output of the relevant stakeholders and from neighboring case studies. Recommendations and a plan were developed to raise the level of harmony and balance between the planning and development of the city of Sharjah and the preservation and management of archaeological sites, specifically in the Al Shuwaihyan historical and artistic area as a case study, and to reduce... Random and ill-considered projects that deviate from the prevailing urban fabric in the region in their design. In addition, a comparison table was made in the indicative regulations between one emirate and another, between the UAE and an Arab country, and finally between the regulations of the UAE and European countries.